Development of Potent and Selective Tissue Transglutaminase Inhibitors: Their Effect on TG2 Function and Application in Pathological Conditions. Issue 10 (22nd October 2015) - Badarau, Eduard; Wang, Zhuo; Rathbone, Dan L.; Costanzi, Andrea; Thibault, Thomas; Murdoch, Colin E.; El Alaoui, Said; Bartkeviciute, Milda; Griffin, Martin
Summary: Potent-selective peptidomimetic inhibitors of tissue transglutaminase (TG2) were developed through a combination of protein-ligand docking and molecular dynamic techniques. Derivatives of these inhibitors were made with the aim of specific TG2 targeting to the intra- and extracellular space. A cell-permeable fluorescently labeled derivative enabled detection of in situ cellular TG2 activity in human umbilical cord endothelial cells and TG2-transduced NIH3T3 cells, which could be enhanced by treatment of cells with ionomycin. Reaction of TG2 with this fluorescent inhibitor in NIH3T3 cells resulted in loss of binding of TG2 to cell surface syndecan-4 and inhibition of translocation of the enzyme into the extracellular matrix, with a parallel reduction in fibronectin deposition. In human umbilical cord endothelial cells, this same fluorescent inhibitor also demonstrated a reduction in fibronectin deposition, cell motility, and cord formation in Matrigel. Use of the same inhibitor in a mouse model of hypertensive nephrosclerosis showed over a 40% reduction in collagen deposition. Graphical Abstract: Highlights: Irreversible tissue transglutaminase (TG2) inhibitors of high selectivity and potency Target the Ca 2+ activated form of TG2 in the intra- and/or extracellular space Reactive with intracellular TG2 and block its translocation into the matrix Effective in blocking hypertensive nephrosclerosis in animal models Abstract : Badarau et al. design and develop high-potency TG2-specific irreversible inhibitors that show reactivity with the intracellular active form of TG2, leading to inhibition of its translocation into the extracellular matrix. The compounds are effective in inhibiting in vitro angiogenesis and hypertensive nephrosclerosis in animal models.